A Sequential Mixed-Methods Study of Pre-Professionals' Understanding of the Undergraduate Music Therapy Internship. (3rd May 2019) - Clements-Cortes, Amy
Abstract: Despite the importance of the clinical music therapy internship, little research has been conducted to understand the perspectives, perceived musical, clinical, and personal skills, concerns, challenges, and anxieties of pre-professionals prior to and upon completion of the internship. This sequential mixed-methods study aimed to assess the perspectives and experiences of undergraduate students in the United States at two stages in the internship in music therapy practice. In total, 177 pre-professionals from the United States participated in this two-part study: (1) an online survey and (2) individual interviews with 25% ( n = 44) of the participants. Survey results indicate statistically significant increases in clinical, musical, and personal skill development from pre- to post-internship. Six broad categories emerged from the interviews: confidence, anxiety, role clarity, professional suitability, loneliness, and boundaries/ethics. The results are encouraging, showing that the internship is a valued clinical experience that fosters improvement in the clinical, musical, and personal skills needed to work as a music therapist. This paper concludes with recommendations and suggestions for educators and supervisors on preparing and supporting pre-professionals in their skill development prior to and during internship.